Breather and double-pole solutions for the Benjamin-Ono equation in a stratified fluid. Issue 2 (2nd April 2016) - Sun, Wen-Rong; Tian, Bo; Zhong, Hui; Liu, Rong-Xiang
Abstract : The Benjamin–Ono equation is hereby investigated, which arises in the context of long internal gravity waves in a stratified fluid. With the Hirota method and symbolic computation, breather solutions are derived. Propagation of the breather and elastic collisions between the breather and soliton are graphically analyzed. The collision period and the bunch number in a wave packet are relevant to the ratio of the real part to the imaginary of the wavenumber. Through the coalescence of wavenumbers in the two-soliton solutions, we obtain the double-pole solutions.